MODIFIKASI PRINSIP PEMERIKSAAN β-D-GLUCAN UNTUK MENDETEKSI CANDIDA ALBICANS DALAM SERUM - Dharmawan, Ruben; Darukutni, Darukutni; Haryati, Sri; Murkati, Murkati; Sari, Yulia; Prasetyo, Afiono Agung (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Candida albicans β-D-glucans examination has been used for invasive fungal detection in human blood and was approved by the Food and Drug Administration. However, the method is rarely used in Indonesia and also because the cost is hardly affordable. A modification of the method using enzymatic reaction is hoped will provide a simple and affordable measurement in human blood serum. β-D-glucans as heterogeneous molecules constitute the major carbohydrates fractions of cell wall and readily detected in supernatants of Candida albicans cultures are hydrolyzed by β glucanase to form D-glucose. This additional glucose is measured using Megazyme GOPOD-Format Procedure® at 510 nm. Candida albicans were identified and cultured was derived from a patient of Dr. Moewardi General Hospital, Surakarta in July, 2012. The results show that β-D-glucans from Candida albicans is measureable to the amount of μg/100 μL serum using this modification principle